The Path and Trends in Information Science and Technology Curriculum Construction - XIONG Zhang; TANG Xiaolan (Jiaoshi jiaoyu xuebao, 2025)
In the process of implementing the new curriculum standards, the construction of Information Science and Technology courses faces challenges in various aspects. Key findings reveal that current reforms should break free from the inertia of traditional exam-oriented education and transition to competency-based and scientific literacy education. Student development should be restructured to prioritize universal accessibility over competition-driven education, while teacher training should focus on enhancing digital literacy and innovative capabilities to foster professional growth. Additionally, the application of AI tools in education requires standardization to establish an ethically grounded and technically robust teaching environment. To address these challenges, this study proposes a people-centered approach to Information Science and Technology curriculum construction, comprising four key strategies: leveraging digital transformation of textbooks to achieve dynamic updates and personalized adaptation of teaching resources; Implementing cross-disciplinary, regionally tailored project-based learning activities to strengthen students' cultural identity and innovative problem-solving skills. A literacy-oriented formative evaluation system is emphasized, utilizing AI technology to enable multidimensional and dynamic assessments. Furthermore, a human-in-the-loop mechanism for digital resource sharing is proposed to promote educational equity and iterative resource optimization. The construction of Information Science and Technology courses should always focus on the comprehensive development of students. Through such approaches as deep integration of multiple disciplines, collaborative development of artificial intelligence education, and project-based practice to assist students' growth an education ecosystem for Information Science and Technology can be constructed to cultivate innovative talents adapted to the future social development.